152k views
2 votes
Given g(x) = g(x)= 3/x^2+2x find g^-1(x)

User Angoru
by
5.5k points

2 Answers

5 votes

Answer: x^3/3+2x^2

hope this helps!!



User Zaxliu
by
5.6k points
4 votes

Answer:


g^(-1)(x)=-1\pm(√(x(x+3)))/(x)

Explanation:

Given :
g(x)= (3)/(x^2+2x)

To find :
g^(-1)(x)

Solution :

We have given the function,


g(x)= (3)/(x^2+2x)

To find inverse let y=g(x)


y= (3)/(x^2+2x)

Replace the value of x and y,


x=(3)/(y^2+2y)

Solve for y,


x(y^2+2y)=3


xy^2+2xy-3=0

Solve by quadratic formula,

i.e. The equation
ax^2+bx+c=0 has solution


x=(-b\pm√(b^2-4ac))/(2a)

On comparing, a=x , b=2x , c=-3


y=(-(2x)\pm√((2x)^2-4(x)(-3)))/(2(x))


y=(-2x\pm√(4x^2+12x))/(2x)


y=(-2x\pm2√(x(x+3)))/(2x)


y=-1\pm(√(x(x+3)))/(x)

Therefore, The inverse of g(x) is


g^(-1)(x)=-1\pm(√(x(x+3)))/(x)

User Torsten Bronger
by
5.4k points